Analisis Pengaruh Celebrity Endorsement Dan Electronic Word Of Mouth (E-Wom) Terhadap Purchase Intention Melalui Brand Hate : (Studi Kasus Pada Starbucks Di Kota Bekasi) - Khoerur Rizky; Dhian Tyas Untari; Heni Rohaeni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to analyze the effect of Celebrity endorsement and Electronic word of mouth (e-WOM) on Purchase intention, as well as investigating the role of Brand hate as an intervening variable. investigate the role of Brand hate as an intervening variable. This research conducted at Starbucks in Bekasi City using a quantitative approach. quantitative approach. The sample of this study consisted of 100 respondents, with primary data obtained through distributing questionnaires to consumers. data obtained through distributing questionnaires to Starbucks consumers in Bekasi through social media. Bekasi through social media. The data was analyzed using the SPSS version 29 application with classical assumption analysis, hypothesis testing, path analysis, and sobel test. The results showed that celebrity endorsement and e-WOM had no effect on brand hate. effect on brand hate, but both have a positive and significant effect on purchase intention. significant on purchase intention. Conversely, brand hate has a negative and significant effect on purchase intention. As an intervening variable intervening variable, brand hate cannot mediate the relationship between celebrity endorsement, e-WOM, and purchase intention.